How to develop adults physical education (voluntary keep-fit gymnastics) (Fiep Bulletin - online, 2015)
Twelve years ago, when the FFGE (French Federation for Educational Gymnastics) was attempting to popularize in France a health and recreational Gymnastics movement for adults – known as “voluntary gymnastics” – we were successful in obtaining from the Executive Committee of this Federation the approval of a text addressed to both educators and the public.